2014
DOI: 10.1073/pnas.1304127111
|View full text |Cite
|
Sign up to set email alerts
|

Accessory factors promote AlfA-dependent plasmid segregation by regulating filament nucleation, disassembly, and bundling

Abstract: In bacteria, some plasmids are partitioned to daughter cells by assembly of actin-like proteins (ALPs). The best understood ALP, ParM, has a core set of biochemical properties that contributes to its function, including dynamic instability, spontaneous nucleation, and bidirectional elongation. AlfA, an ALP that pushes plasmids apart in Bacillus, relies on a different set of underlying properties to segregate DNA. AlfA elongates unidirectionally and is not dynamically unstable; its assembly and disassembly are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 29 publications
4
43
0
Order By: Relevance
“…4C, Inset). The initial slope when plotting scattering signal vs. time on a double-logarithmic scale yields the number of steps required for the formation of a growing filament (19,25). Indeed, TubRC changed the slope of the initial polymerization signal, further supporting the finding that TubZ filaments nucleate by fewer steps when TubRC is present than with TubZ alone (Fig.…”
Section: Tubrc Supports the Seeding Of Tubz Filamentssupporting
confidence: 67%
See 1 more Smart Citation
“…4C, Inset). The initial slope when plotting scattering signal vs. time on a double-logarithmic scale yields the number of steps required for the formation of a growing filament (19,25). Indeed, TubRC changed the slope of the initial polymerization signal, further supporting the finding that TubZ filaments nucleate by fewer steps when TubRC is present than with TubZ alone (Fig.…”
Section: Tubrc Supports the Seeding Of Tubz Filamentssupporting
confidence: 67%
“…In vitro, TubZ assembles into two-and four-stranded polymers (13)(14)(15)(16), and structural studies suggested that the centromeric TubRC complex forms a ring-like structure (17), interacting with the long C-terminal TubZ extensions (18). Thus, it was proposed that the TubRC complex tracks growing ends of TubZ filaments in analogy to the centromeric complex that follows growing filament ends of the actin-like partitioning systems (5,6,19). In bulk assays, TubRC has been reported to enhance TubZ filament formation, possibly indicating a switch in dynamic behavior (17,20).…”
mentioning
confidence: 99%
“…As an example, wild-type actin elongates bidirectionally from meromyosin-labeled stable seeds (left) (Woodrum, Rich, & Pollard, 1975). AlfA (right) seeds with wild-type protein growing from a streptavidin-labeled seed (Polka, Kollman, Mullins, 2014). (A) AlfA images from Polka et al (2009).…”
Section: Figure 21mentioning
confidence: 99%
“…This inherent instability of ParM filaments produces a high concentration of monomeric ParM that is available to do polymerization-coupled work. Interestingly, another DNA-segregating ALP, AlfA, has a remarkably different set of assembly properties from ParM: (1) it is not inherently dynamically unstable (Polka et al, 2009), (2) its nucleation is controlled by accessory factors (Polka, Kollman, Mullins, 2014), (3) its elongation is polarized (Polka, Kollman, Mullins, 2014), and (4) it strongly self-associates and forms large filament bundles (Polka et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Reconstitution of all three components in vitro demonstrated that AlfB/parN complexes ride on the ends of elongating bundles and also move along existing bundles in both directions. Continued growth at AlfB/parN is ensured by free AlfB repressing AlfA polymerization elsewhere in the cell (32) (Fig. 1).…”
Section: We Are All Snowflakes: the Diversity Of Bacterial Polymersmentioning
confidence: 99%